1954
DOI: 10.1098/rspa.1954.0017
|View full text |Cite
|
Sign up to set email alerts
|

High-angle Kikuchi patterns

Abstract: A cylindrical specimen chamber and camera have been used to study the high-angle Kikuchi patterns obtained by reflexion of electrons, of energy 6 to 50 keV, from the cleavage surfaces of crystals with the sodium chloride structure. Angles of scattering ranging from 0 to 164° were covered. The relative intensity of the pattern at different scattering angles was measured using a photographic technique. The intensity distribution was found to become less steep as the energy of the incident electrons decreased. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

1955
1955
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(18 citation statements)
references
References 1 publication
1
17
0
Order By: Relevance
“…Among them are those of Shinohara & Matsukawa (1933), Boersch (1937 and Pfister (1953), who observed that Kikuchi bands in transmission patterns change from defect to excess, or vice versa, with the change of the energy of the incident electrons and with the change of the thickness of the crystal. Alam, Blackman & Pashley (1954) observed a similar effect for the intensities of Kikuchi bands in reflexion patterns when the angle of incidence is changed. The failure of the present theory to cover these observations is due to our assumption that ~i(r) is very small compared with q%(r).…”
Section: (B) Effect Of Absorptionsupporting
confidence: 57%
“…Among them are those of Shinohara & Matsukawa (1933), Boersch (1937 and Pfister (1953), who observed that Kikuchi bands in transmission patterns change from defect to excess, or vice versa, with the change of the energy of the incident electrons and with the change of the thickness of the crystal. Alam, Blackman & Pashley (1954) observed a similar effect for the intensities of Kikuchi bands in reflexion patterns when the angle of incidence is changed. The failure of the present theory to cover these observations is due to our assumption that ~i(r) is very small compared with q%(r).…”
Section: (B) Effect Of Absorptionsupporting
confidence: 57%
“…patterns (Alam et al, 1954;Venables and Harland, 1972;Dingley, 1981;; Dingley and Baba-Kishi, SELECTED area electron channelling patterns (Coates, 1990;Dingley and Randle, 1992;Randle, 1992;Day, 1967;Joy, 1974;Joy et al, 1982;Davidson, 1984; both provide quantitative data concerning Lloyd, 1985;1987;Schmidt and Olesen, 1989; Lloyd spatial variation of crystallographic orientations Lloyd, 1995) and electron backscatter minerals. In many problems relevant to geologists, Mineralogical Magazine, December 1996, Vol.…”
Section: Introductionmentioning
confidence: 99%
“…Scanning across ferroelectric domains will result pattern geometry and intensity variations which may be detected by our TLD detector sampling a small area of the pattern. Support for this idea comes from the early EB diffraction work of Alam et al, 27 which demonstrates that the commonly used electron backscatter diffraction orientation (EB ~70° incidence to surface normal) produces strong scattering but those patterns also exist at high angles back along the incident beam direction. For all EB diffraction from bulk samples there is combined diffuse and elastic scattering, which gives rise to the Kikuchi bands in diffraction patterns.…”
Section: Discussionmentioning
confidence: 84%